2021
DOI: 10.1109/tcsvt.2021.3074312
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Screen Content Support in VVC: Applications, Coding Tools, and Performance

Abstract: In an increasingly connected world, consumer video experiences have diversified away from traditional broadcast video into new applications with increased use of non-cameracaptured content such as computer screen desktop recordings or animations created by computer rendering, collectively referred to as screen content. There has also been increased use of graphics and character content that is rendered and mixed or overlaid together with camera-generated content. The emerging Versatile Video Coding (VVC) stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Generally speaking, screen content is an umbrella-term of the computer-generated or rendered data characterized with noise-free, sharp-edges and high contrast [1]. In the past decades, a series of efforts have been dedicated to improve the compression performance of the screen content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, screen content is an umbrella-term of the computer-generated or rendered data characterized with noise-free, sharp-edges and high contrast [1]. In the past decades, a series of efforts have been dedicated to improve the compression performance of the screen content.…”
Section: Introductionmentioning
confidence: 99%
“…The screen content coding tools could seamlessly collaborate with the scene characteristic and the coding characteristic of screen content. It was reported that the screen content coding tools could bring additional 33.22% BD-Rate savings [1], laying the foundation of versatile usage of the VVC.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the observation and minimum entropy principle, value range C is divided into multiple subranges for optimal coding and binarization. For the string lengths of Evs and Ups, there are eleven subranges, which are the intersection of C and [0,1), [1,2), [2,4), [4,8), [8,16), [16,32), [32,64), [64,128), [128,256), [256,512), and [512,1024), respectively, that is,…”
Section: Optimized Coding Methods For String Lengthmentioning
confidence: 99%
“…With more and more popular applications using computer screen as interfaces for daily remote human-machine and human-human interactions, such as online education, teleconferencing, telecommuting, and remote entertainment, almost all recent video coding standards have included screen content coding (SCC) tools [1]. The video coding standards with SCC tools include high efficiency video coding (HEVC), versatile video coding (VVC) [2], the secondgeneration audio video standard (AVS2), the third-generation AVS (AVS3) [3], [4], AV1, and essential video coding (EVC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation